Radiofrequency power amplifiers in horizontal current bipolar transistor technology : doctoral thesis - Osrečki, Željko (Ž. Osrečki ; Faculty of electrical engineering and computing, 2021)
The large-signal performance of the horizontal current bipolar transistor (HCBT) is investigated by extensive measurements and simulations, and its suitability for the radiofrequency power amplifier design is demonstrated by designing advanced high-efficiency and wideband power amplifiers. An accurate and calibrated scalar load-pull setup is firstly employed for the determination of the optimal input and output matching impedances for different HCBT structures to achieve the maximum output power. The HCBT in Class-AB regime at the fundamental frequency of 2.4 GHz provides up to 25 dBm output power with the gain of 11 dB, exhibiting optimal matching impedances close to 50 Ω. The suitability of different collector region designs is investigated by performing load-pull measurements for the HCBTs with uniform, n-well, and low-doped collectors, where the low-doped HCBT achieves the highest gain, whereas the n-well HCBT provides the highest collector efficiency in the power back-off power range. Due to its robustness in large-signal operation, the HCBT is analyzed in the regime where the load line penetrates the impact ionization region, for the base-emitter bias applied by either a voltage or current source. Additionally, the boundary of linear operation is found for the HCBT by developing a dedicated vector load-pull setup with the possibility of a time-domain waveform measurement in large-signal operation. A high-efficiency Doherty power amplifier is designed using discrete HCBTs at 2.4 GHz, where the amplifier achieves 38.7% collector efficiency with the modulated excitation of 3.5-dB peak to average power ratio. Finally, a wideband balanced amplifier with 700-MHz bandwidth at 2.4 GHz is designed, exhibiting efficiency greater than 35.6% over the bandwidth. The amplifiers provide a performance surpassing that of the most advanced power amplifiers implemented in costlier semiconductor technologies. Keywords: horizontal current bipolar transistor (HCBT), bipolar transistors, large-signal, scalar load-pull, vector load-pull, waveform measurement, linear operating area, power amplifiers, Doherty, balanced.